Intusussception Secondary to Gastrointestinal Foreign Body in an Eleven Month old Juvenile African Lion (Panthera Leo) Case Report - Ajadi R. A.; Egbetade A. O.; Ajayi O. O.; Makinde O. A.; Okandeji M. E. (Folia Veterinaria, 2019)
An eleven month old male, juvenile lion brought for rehabilitation at the Olusegun Obasanjo Presidential Library (OOPL) Wildlife Park was diagnosed with gastrointestinal foreign body and intussusception based on the history of persistent vomiting following ingestion of a cotton towel, and radiographic findings of a radiopaque gastric foreign body extending from the fundus to the pylorus and a cylindrical soft tissue mid-abdominal mass. The lion was premedicated with an intramuscular injections of ketamine (5 mg.kg−1) and midazolam (0.25 mg.kg−1), while anaesthesia was induced with an intravenous injection of propofol (2 mg.kg−1). A celiotomy followed by gastrotomy and subsequent intestinal resection and anastomosis was performed to remove the gastrointestinal foreign bodies and correct the intussus ception. The lion recovered well without any complication and was gradually introduced back into the group housing three weeks later following successful alimentation process. This report is probably the first case of intussusception in a lion that was associated with a gastrointestinal foreign body.